The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s13071-019-3871-3
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific differences in Toxoplasma gondii, Neospora caninum and Besnoitia besnoiti seroprevalence in Namibian wildlife

Abstract: Background: Knowledge about parasitic infections is crucial information for animal health, particularly of free-ranging species that might come into contact with livestock and humans. Methods:We investigated the seroprevalence of three tissue-cyst-forming apicomplexan parasites (Toxoplasma gondii, Neospora caninum and Besnoitia besnoiti) in 506 individuals of 12 wildlife species in Namibia using in-house enzyme linked immunosorbent assays (indirect ELISAs applying purified antigens) for screening and immunoblo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 71 publications
1
42
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of isolated viable T. gondii from caracal. This is also the first study to document T. gondii cysts directly from the striated muscles of caracals; however earlier studies only detected the antibodies to T. gondii in caracals ( Serieys et al, 2019 ; de Camps et al, 2008 ; Zhang et al, 1991 , 2001 ; Shi et al, 1992 ; Spencer et al, 2003 ; Gomez-Rios et al, 2019 ; Seltmann et al, 2020 ; Dubey et al, 2010 ). In this study, isolation T. gondii stain from caracal case # 1 was unsuccessful.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first report of isolated viable T. gondii from caracal. This is also the first study to document T. gondii cysts directly from the striated muscles of caracals; however earlier studies only detected the antibodies to T. gondii in caracals ( Serieys et al, 2019 ; de Camps et al, 2008 ; Zhang et al, 1991 , 2001 ; Shi et al, 1992 ; Spencer et al, 2003 ; Gomez-Rios et al, 2019 ; Seltmann et al, 2020 ; Dubey et al, 2010 ). In this study, isolation T. gondii stain from caracal case # 1 was unsuccessful.…”
Section: Discussionmentioning
confidence: 85%
“…Chickens, rabbits, raw pork and beef are the main food for captive caracals. Currently, only some studies reported the presence of seroconversion antibody to T. gondii in caracals ( de Camps et al, 2008 ; Spencer et al, 2003 ; Gomez-Rios et al, 2019 ; Serieys et al, 2019 ; Seltmann et al, 2020 ; Dubey et al, 2010 ). Varied rate of T. gondii infection has been documented in caracals around the world ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we applied a bacterially expressed biotinylated recombinant TgSAG1 [37], the major surface antigen of T. gondii tachyzoites [24], which is used widely for serodiagnosis in humans, but also in wild or livestock animals (e.g. [47][48][49][50][51][52][53][54][55]). Our recombinant TgSAG1 bio is unique in that it allows an oriented and reproducible coupling of the antigen to streptavidincoated magnetic Luminex beads via a single C-terminal biotin [37].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we applied a bacterially expressed biotinylated recombinant TgSAG1 [37], the major surface antigen of T. gondii tachyzoites [24], which is used widely for serodiagnosis in humans, but also in wild or livestock animals (e.g. [47][48][49][50][51][52][53][54][55]). Our recombinant TgSAG1 bio is unique in that it allows an oriented and reproducible coupling of the antigen to streptavidin-coated magnetic Luminex beads via a single C-terminal biotin [37].…”
Section: Discussionmentioning
confidence: 99%